1998
DOI: 10.1046/j.1365-2540.1998.00316.x
|View full text |Cite
|
Sign up to set email alerts
|

The genetic basis of host plant adaptation in the brown planthopper (Nilaparvata lugens)

Abstract: We studied the genetic architecture of host plant adaptation in two populations of brown planthopper Nilaparvata lugens (Homoptera: Delphacidae): one feeding on cultivated rice Oryza sativa and the other feeding on a weed grass Leersia hexandra. Proportional weight change, survival and development time of inbred Leersia-and rice-feeding lines, F 1 , F 2 , and backcross classes have been examined. Most of the performance differences among populations seem to be controlled by a few genes. Dominance of rice popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 29 publications
4
34
0
Order By: Relevance
“…One reason for this lack of clarity is that empirical data for the genetics of ecological adaptation vary among species (e.g., governed by autosomal loci or sex-linked genes, few or many genes, genes of small or large effect, or genes with dominance, epistatic interactions or no dominance)15. However, the present results and a growing number of studies have demonstrated that phytophagous insects have different genetic bases between preference and performance with different modes of inheritance7816171819202122. This implies that hybrids are likely to express different, and often functionally incompatible, phenotypes for preference and performance traits.…”
Section: Discussionmentioning
confidence: 56%
“…One reason for this lack of clarity is that empirical data for the genetics of ecological adaptation vary among species (e.g., governed by autosomal loci or sex-linked genes, few or many genes, genes of small or large effect, or genes with dominance, epistatic interactions or no dominance)15. However, the present results and a growing number of studies have demonstrated that phytophagous insects have different genetic bases between preference and performance with different modes of inheritance7816171819202122. This implies that hybrids are likely to express different, and often functionally incompatible, phenotypes for preference and performance traits.…”
Section: Discussionmentioning
confidence: 56%
“…Moreover, compared with SfGSTd1 , NlGSTd1 showed a similar expression pattern across the six life stages (five nymph stages and the macropterous adult male stages) (Figure 7) and is similar to the LsGSTd1 in L. striatellus [18]. This difference in GST expression could be due to the breadth of host plants used by the three species, with N. lugens being monophagous, while L. striatellus and S. furcifera are polyphagous [51].…”
Section: Discussionmentioning
confidence: 81%
“…Our findings thus establish the use of single males to found experimental populations as an attractive option for BSA studies in mites. This is of particular relevance to potential genetic studies of polygenic traits, examples of which include many instances of metabolic pesticide resistance (Li et al, 2007; Van Leeuwen et al, 2010), and presumably host plant adaptation (Dermauw et al, 2013; Gould, 1979; Jaquiéry et al, 2012; Sezer and Butlin, 1998; Via, 1990), where locus and allelic heterogeneity can confound the detection of quantitative trait loci.…”
Section: Discussionmentioning
confidence: 99%